Collagen Content and Collagen Fiber Architecture in the Skin of Shamo Chicken, a Japanese Game Fowl - Shotaro Nishimura; Sayaka Arai; Yoshinao Z Hosaka (The Journal of Poultry Science, 2023)
Collagen content and collagen fiber architecture in the skin of Shamo chickens were compared between sexes and body parts. Cervical, thoracic, dorsal, femoral, and crural skin samples were collected and their collagen content was analyzed. Collagen fiber specimens were prepared for scanning electron microscopy using the cell maceration method with a NaOH solution. Sex differences in collagen content were only observed in the femoral skin of mature chickens, but not in 10-week-old chicks. The difference in collagen content between body parts was obvious; femoral and crural skin had higher collagen content than those of other parts in both sexes. Scanning electron microscopy indicated that the collagen fiber architecture was quite different between the superficial and deep layers in the dermis, with the former consisting of loosely tangled band-like collagen fibers, and the latter composed of thick and dense layers of collagen bundles in a parallel arrangement. The width of collagen fibers in the superficial layer of the dermis differed between sexes in the dorsal, femoral, and crural skin. From these results, it is likely that the difference in collagen content in the femoral skin is not due to sex hormones but other factors, such as mechanical stimulation in daily activity. Additionally, collagen fiber width in the superficial layer is likely related to the difference in collagen content between sexes and between body parts.